Estimating the modulatory effect of cadmium chloride on the genotoxicity and mutagenicity of silver nanoparticles in mice - Mohamed, H. R. H. (Cellular and Molecular Biology, 2017)
Silver (Ag) nanoparticles (nano-Ag) are widely used because of their distinctive antimicrobial properties, but this widespread use increases Ag release into the environment along with many other pollutants such as heavy metals. Therefore, this study was undertaken to study the modulatory effect of cadmium chloride (CdCl2) on the genotoxicity and mutagenicity of nano-Ag in mice liver, kidney and brain tissues. Co-injections of CdCl2 (1.5 mg/kg) with nano-Ag (20, 41, or 82 mg/kg) resulted in significant elevations in both single and double DNA strand breaks that triggered higher apoptotic DNA damage, as revealed by the more fragmented appearance of genomic DNA and the significant increase in apoptotic fractions. Concurrent higher mutation incidence in the presenilin-1 and p53 genes was observed after CdCl2 co-treatment than in nano-Ag-treated groups. Immuno-histochemical localization of p53 protein revealed the overexpression of the p53 gene and the histological examination showed diffusely degenerated, congested blood vessels and the infiltration of leukocytes in the liver, kidney, and brain tissues of the groups co-treated with nano-Ag and CdCl2. Moreover, CdCl2 co-injection with nano-Ag increased reactive oxygen species (ROS) generation, as revealed by increased malondialdehyde levels, decreased glutathione levels, and decreased superoxide dismutase and glutathione peroxidase activity, compared with those induced by nano-Ag particles alone. We concluded that CdCl2 enhanced the nano-Ag-induced genotoxicity via increasing mutation incidence in p53 and presenilin-1 gene.